EFFECT OF COMMUNITY AND INFRASTRUCTURAL ISSUES ON OPERATIONAL EFFICIENCY OF OIL AND GAS ORGANIZATIONS IN KENYA - Mobutu , James; Nzulwa, Joyce; Nzulwa, Joyce (European Journal of Business and Strategic Management, 2021)
Purpose: The study investigated effect of community and infrastructural issues on operational efficiency of oil and gas organizations in Kenya Methodology: This study applied descriptive research design and employ exploratory research to explore the variables. The population of interest in this study comprised of 37 selected entities involved in exploration. The 37 entities formed the study units from which respondents were drawn from community liaison, management, operations, quality and security departments giving a target population of 148 respondent. Findings: Results indicated the significant and challenging issues faced by exploration organizations are diverse and dispersed in their nature. The exploration organizations have to face the risks whether they emanate internally or externally as they operate or envision to operate in Kenya. Unique Contribution to Theory Practice and Policy: The study points out that organizational changes should be based on reducing the impact of risk factors and is in line with the postulates of theory of constraints theory that drove this study. This theory is general and useful only as a technique for scheduling intermittent production systems to make operations lean. Operational managers need to visit research papers to ascertain what the contributors to their performance metrics are.